2017
DOI: 10.4172/2161-1165.1000302
|View full text |Cite
|
Sign up to set email alerts
|

Food Handling Practices and Associated Factors among Food Handlers in Arba Minch Town Public Food Establishments in Gamo Gofa Zone, Southern Ethiopia

Abstract: Background: Food borne diseases are common in developing countries including Ethiopia because of the prevailing poor food handling and sanitation Practices. Food handlers play an important role in ensuring food safety throughout the chain of production, processing, storage and preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
60
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(85 citation statements)
references
References 7 publications
15
60
10
Order By: Relevance
“…It is higher than mothers in Debarq town [41], public food establishments in northwest Ethiopia [42], and Araba minch [43]. Moreover,it is higher, compared to unaggregated responses like handle money while receiving customers in Gondar butcher shops (45.3%) [9], wearing an apron during work (38.3%) [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is higher than mothers in Debarq town [41], public food establishments in northwest Ethiopia [42], and Araba minch [43]. Moreover,it is higher, compared to unaggregated responses like handle money while receiving customers in Gondar butcher shops (45.3%) [9], wearing an apron during work (38.3%) [7].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the result of this study is also lower than studies conducted in Mekelle (63.9%), 8 Dangla (52.5%), 22 Dire Dawa (52.4%) 23 and Gamogofa (32.6). 24 The difference might be due to study setting, sensitive environment, and educational status of respondents. The study in Mekelle was conducted on the university campus.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the food handlers being responsible to ensure food safety and hygiene in public food establishments, little is known about their level of food handling practices and the associated factors among establishment workers in the study area. Few previous Ethiopian studies conducted in Arbaminch, Diredawa and Debarq town revealed that the prevalence of good food handling practice was 32.6%, 52.4%, and 40.1%, respectively [19][20][21]. Therefore, it is important to conduct a repeated study aiming to assess food handling practice and associated factors among food handlers working in public food establishments in Woldia tow, Northeast Ethiopia.…”
Section: Introductionmentioning
confidence: 99%